Ilustratīvā materiāla atveide „Mūsdienu latviešu valodas vārdnīcā” - Zuicena, Ieva (Baltistica, 2012)
THE QUESTION OF ILLUSTRATIVE EXAMPLES IN EXPLANATORY DICTIONARIES AND THE DICTIONARY OF CONTEMPORARY LATVIAN LANGUAGESummaryThere are two kinds of illustrative examples that are used in explanatory dictionaries: quotations and combination of words (phrases). Quotations are usually included in large dictionaries of many volumes, but phrases are popular in ordinary explanatory dictionaries.In explanatory dictionaries illustrative examples have several functions: 1) to confirm that a corresponding word really exists in language; 2) to demonstrate how the word is used in a context; 3) to supply with additional information.In the Dictionary of Contemporary Latvian Language illustrative examples are mainly given in the form of phrases, although sometimes quotations are also used, because there are several word groups that need a larger context (e.g., words with a figurative meaning, stylistically marked words or meanings, interjections).
Keywords: Latvian; lexicology; lexicography; Dictionary of Contemporary Latvian